Elementary Students Perception Towards the Use of Songs in English Language Learning - Stephanie Gloria Amanda Tauran (Al-Qalam Institue, 2025)
This study investigates elementary students’ perceptions of using songs in English language learning, exploring how songs affect vocabulary acquisition, pronunciation, listening comprehension, and overall student engagement. The background highlights the growing trend of incorporating music into language instruction, yet there is a gap in understanding how younger students perceive its effectiveness. A quantitative research design with a descriptive approach was employed, utilizing a questionnaire to gather data from 30 Grade 5 students at a private elementary school in Manado. The results indicate that students perceive songs as a highly effective and enjoyable tool for learning English, with a mean score of 4.61, reflecting strong agreement on their impact on vocabulary and pronunciation. However, some students expressed concerns about the long-term retention of vocabulary and the limited contribution of songs to grammar and speaking fluency. The study concludes that while songs enhance motivation and specific language skills, a more integrated approach combining songs with other methods is necessary for comprehensive language acquisition. This research contributes valuable insights into the pedagogical value of music-based instruction in language learning and offers practical recommendations for educators.